Psychological considerations in the education of Nigerian women (1998)
This paper brings together under one umbrella many of the psychological factors that have been found to affect the education of women especially in Nigeria. The paper looks at factors that are inherent in andrelate to the psychology of the Nigerian woman. The writer used the focus group discussion method, and reports here ten psychological issues which must be taken into consideration. These are attitude, motivation, perception,sensitivity, intelligence, confirmation of capacity to learn, self doubt, self involvement, fear of consequences of success and feelings of inferiority. Certain questions were raised for further research, and the conclusion zeroed in on the need for therapeutic interventions that will support the woman's ego strengths, help her focus more clearly on realites, thus encouraging thoughful independence. It is the achievement of the latter that will enable her participate more meaningfully in education and achieve maximally.